An investigation into applicant reactions to online testing: perceptions towards feedback provision in occupational selection - Martin, Christopher (2021)
A main aim of this doctoral research was to examine job applicant reactions towards online testing, and specifically different forms of feedback provision. As job recruitment is a `bilateral process` with the recruiters aiming to employ a candidate, and from the candidate`s perspective the feedback provision and selection process may indicate the employer`s future behaviour in determining whether they accept a job offer. The research is underpinned by organisational justice theory and by Gilliland’s (1993) organisational justice model. This model considers how elements of procedural and distributive justice interact and examines the effect such fairness reactions have in terms of individual and organisational outcomes.